DNA barcoding and biochemical profiling of medicinal plants of northern and desert areas of Pakistan to improve rural living standard - Jamil, Amer; Ashfaq, Muhammad (International Food Policy Research Institute, 2016)
Pakistan is a country with a varied climate and hosts a large number of medicinal plant species. Most of the medicinal plants are collected in the wild by local communities. These plants are an important source of livelihood for rural economies. However, no systematic documentation has been undertaken to assist in proving ownership of the plant resources. This project focused on the conservation of natural plant resources by using modern molecular techniques and creating awareness for determining the active ingredients of the plants through biochemical profiling. Further objectives of the study were to identify marketing channels for medicinal plants, costs and margins of stakeholders involved in the marketing of medicinal plants, and factors responsible for the poor trade and decreasing population of these plants in the two study areas of Swat Valley and Cholistan Desert.